Use of Short Term Ventilation Tube in Children Having Chronic Otitis Media with Effusion - Ahmed Mohammed Al-Alwan; Sura Kadhim; Haider Wahab Alsarhan (Wolters Kluwer Medknow Publications, 2024)
Background: Otitis media with effusion is a collection of fluid inside the middle ear cleft, treatment of this condition include medical and surgical methods. This research goal is to focus and specify the clinical features of OME and the association between the new staging and the postoperative findings after surgery of insertion of ventilation tubes (VTs). Objectives: The objective of the study was to assess postoperative sequelae after VT insertion in children. Patients and Methods: Thirty two children with OME with surgical insertion of short term ventilation tubes were included in this study and followed up for one year. Results: In 22 patients, the fluid aspirated surgically after myringotomy was serous, whereas 10 patients were mucinous; for the patients, 53.12% had recurrence, whereas 46.88% showed no recurrence of OME. Only 6.25% of cases included in this study developed myringosclerosis; no otorrhea was reported during the period of the presence of VT in the tympanic membrane, no persistent tympanic membrane perforation after VT auto-extrusion. Conclusion: Even though VT have shown to be very useful in solving conductive hearing loss, its efficacy is a matter of debate in preventing long-term poor effects of the tympanic membrane and delayed onset of hearing loss. Even though ventilation tubes have shown to be very useful in solving the problem of conductive hearing loss.